2009
DOI: 10.2478/v10096-009-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

The Saxo-Danubian Granite Belt: magmatic response to post-collisional delamination of mantle lithosphere below the southwestern sector of the Bohemian Massif (Variscan orogen)

Abstract: Abstract:On the basis of the synchronicity of geochronological data and the similarity of granite types, it is proposed that the mid-Carboniferous Fichtelgebirge/Erzgebirge Batholith in the Saxothuringian Zone of the central European Variscan Fold Belt and the South Bohemian Batholith in the Moldanubian Zone (including the intervening Oberpfalz and Bavarian Forest granite areas) belong to one coherent and cogenetic, ca. 400 km long plutonic megastructure. Unlike older (syn-collisional) plutonic structures in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…Also Siebel et al (2003) found that mantle-related magmatism in NE Bavaria postdated the final convergence stage of the Variscan orogen (see also Finger et al 2009). …”
Section: Variscan Magmatismmentioning
confidence: 99%
“…Also Siebel et al (2003) found that mantle-related magmatism in NE Bavaria postdated the final convergence stage of the Variscan orogen (see also Finger et al 2009). …”
Section: Variscan Magmatismmentioning
confidence: 99%
“…The batholith belongs to one coherent and cogenetic, ca. 400 km long plutonic megastructure of the Saxo-Danubian Granite Belt [14].…”
Section: Geological Settingmentioning
confidence: 99%
“…Partial melting of metapelites produced biotite granites-granodiorites of the Weinsberg suite (331-323 Ma), S-type two-mica granites of the Eisgarn suite (329-324 Ma), and fine-to medium-grained I/S-type biotite granites-granodiorites of the Freistadt/Mauthausen suite . The Rastenberg and Knížecí Stolec plutons (337)(338)(339)(340) are part of the durbachitic granites belt; also different diorites form small isolated bodies (323-327 Ma) within the Moldanubian Batholith (e.g., Gebharts diorites) (Frasl and Finger 1988;Liew et al 1989;Vellmer and Wedepohl 1994;Klötzli and Parrish 1996;Finger et al 1997Finger et al , 2009Gerdes et al 2000Gerdes et al , 2003Siebel et al 2008;Žák et al 2011;Verner et al 2008Verner et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…One of the classic examples is the Variscan Belt in Europe, produced as a result of the late Palaeozoic convergence of Gondwana and Laurussia. The Moldanubian Batholith (MB) that forms one of the largest plutonic complexes within the European Variscan Belt, covering 10 000 km 2 in the central and western parts of the Moldanubian Zone of Bohemian Massif (an easterly exposure of the European Variscan Belt), provides an excellent insight into the origin and emplacement of such crustally derived magmas (e.g., Liew et al 1989;Holub et al 1995;Gerdes et al 2000;Finger et al 2009;Verner et al 2014).…”
Section: Introductionmentioning
confidence: 99%